Answer:
45.3 mm
Step-by-step explanation:
Use the basic 45-45-90 triangle with side length 1 as the building block here. If the length of one side is 1, then the perimeter is 1 + 1 + 1 + 1, or 4, and the length of the diagonal is √2.
We are told that the length of the diagonal of the given square is 16 m.
Determine the length of one side of this square, using an equation of proportions:
16 x
------ = -------
√2 1
16
Then (√2)x = 16, and x = -----------
√2
The perimeter of the given square (with diagonal 16 mm) is 4 times the side length found above, or:
16 16
4 ---------- = (2)(2) ----------- = (2)(√2)(16) = 32√2 (all measurements in mm)
√2 √2
This perimeter, rounded to the nearest tenth, is 45.3 mm.
Answer:
x²-10x=area
Step-by-step explanation:
Area= length×width
Length: x
Width: x-10
Area= x(x-10)= x²-10x
I hope this helps...
:)
Answer:
The standard deviation of X is 0.7
Step-by-step explanation:
We are given the following distribution:
x: 0 1 2 3
P(x): 0.3 0.5 0.2 0.4
We have to find the standard deviation of X.
Formula:
![E(x) = \displaystyle\sum x_iP(x_i)\\\\E(x) =0(0.3) + 1(0.5) + 2(0.2) + 3(0.4)\\\\E(x) = 2.1\\\\E(x^2) = \displaystyle\sum x_i^2P(x_i)\\\\E(x^2) =0(0.3) + 1(0.5) + 4(0.2) + 9(0.4)\\\\E(x^2) = 4.9\\\\Var(x) = E(x^2) - (E(x))^2 = 4.9-(2.1)^2 = 0.49\\\\\sigma(x) = \sqrt{Var(x)} =\sqrt{0.49} = 0.7](https://tex.z-dn.net/?f=E%28x%29%20%3D%20%5Cdisplaystyle%5Csum%20x_iP%28x_i%29%5C%5C%5C%5CE%28x%29%20%3D0%280.3%29%20%2B%201%280.5%29%20%2B%202%280.2%29%20%2B%203%280.4%29%5C%5C%5C%5CE%28x%29%20%3D%202.1%5C%5C%5C%5CE%28x%5E2%29%20%3D%20%5Cdisplaystyle%5Csum%20x_i%5E2P%28x_i%29%5C%5C%5C%5CE%28x%5E2%29%20%3D0%280.3%29%20%2B%201%280.5%29%20%2B%204%280.2%29%20%2B%209%280.4%29%5C%5C%5C%5CE%28x%5E2%29%20%3D%204.9%5C%5C%5C%5CVar%28x%29%20%3D%20E%28x%5E2%29%20-%20%28E%28x%29%29%5E2%20%3D%204.9-%282.1%29%5E2%20%3D%200.49%5C%5C%5C%5C%5Csigma%28x%29%20%3D%20%5Csqrt%7BVar%28x%29%7D%20%3D%5Csqrt%7B0.49%7D%20%3D%200.7)
Thus, the standard deviation of X is 0.7
Answer:
f(g(0) )= -1
Step-by-step explanation:
Find g(0) = -1
Then find f(-1) = 1
f(g(0) )= -1
Yes, it is.
2(3) - 3(2) = 0
2(3) + 2 = 8